Innovative business approaches for the reduction of extreme poverty and marginality? - Heike Baumüller; Christine Ladenburger; Joachim von Braun (University of Bonn, Center for Development Research (ZEF), 2011)
Extreme poverty is an immense political and market failure, wasting the potential of hundreds of millions of people. Investing in the creation of markets that include the extreme poor and marginalized should thus not only be considered as a charitable activity, but promises high returns on investments - in financial and humanitarian terms. However, while the potential of innovative business approaches to target the poor that live close to the poverty line is increasingly being recognised, the question remains how far these approaches can push the margin to also include those that are extremely poor. And how can those that are marginalized from development opportunities be brought into and benefit from market-based systems to improve the quality of their lives? The impressive rise of business approaches to combating poverty stems from a long history of debates on the role of businesses in society. From an initial focus on social objectives as an external add-on, leading business thinkers have increasingly been stressing the benefits for companies of integrating social considerations into their core business strategies, for instance by targeting lowincome consumers (or 'bottom of the pyramid' markets) or strengthening supply and distribution chains through the involvement of local communities as part of inclusive business strategies. Others - most notably Muhammed Yunus along with other social entrepreneurs - are taking this argument one step further, advocating the use of business strategies primarily to address social goals rather than for financial gains. Thus, in discussions on the role of business in society, profit maximisation as the primary objective of business operations is increasingly making way for business initiatives that are guided by social objectives. This trend is also being supported by growing interest among investors in financing enterprises that promote social or environmental objectives, either as their primary aim or in parallel with seeking to generate financial returns. How suitable these different approaches are to engage the poorest and marginalized depends in part on the extent to which they are able to involve the extreme poor themselves, their flexibility to direct business objectives towards the reduction of extreme poverty and marginality, and their ability to successfully operate with non-business public and civil society partners and in sectors of particular interest to the extreme poor. Further research and action is needed to identify outcome-focused indicators and measurement tools for social value creation, examine possible government measures to support business activities for the poorest, and consider complementarities between the different business approaches. While we recognise that it is unrealistic to expect businesses to be able to reach all of the extreme poor, we believe that the boundaries of innovative business operations can be pushed much further to include a far larger number of the poorest and marginalized.
Keywords: 330; Marginality; extreme poverty; social value; corporate social responsibility; bottom of the pyramid; inclusive business; social entrepreneurship; impact investing